Whole-genome resequencing reveals the origin of tea in Lincang - Lei, Yahui; Yang, Ling; Duan, Shengchang; Ning, Siqi; Li, Dawei; Wang, Zijun; Xiang, Guisheng; Yang, Ling; Wang, Chunping; Zhang, Shiyu; Zhang, Shuangyan; Ye, Shuang; et al. (Frontiers in Plant Science, 2022)
Phylogeographic, population genetics and diversity analysis are crucial for local tea resource conservation and breeding programs. Lincang in Yunnan has been known as the possible place of domestication for tea worldwide, yet, its genetic makeup and unique Lincang origin are little understood. Here, we reported a large-scale whole-genome resequencing based population genomic analysis in eight main tea-producing areas of Lincang in Yunnan (1,350 accessions), and the first comprehensive map of tea genome variation in Lincang was constructed. It was observed that these eight areas of Lincang have similar genetic backgrounds, and the hybrid between tea accessions was noticeable, resulting in insignificant genetic differentiation between geographical populations and low genetic diversity. We also found that Xigui and Nahan Tea Mountain in Linxiang, Baiying Mountain Ancient Tea Garden in Yun, and Jinxiu Village of Xiaowan Town in Fengqing were all likely to be the origin center of Lincang tea. The findings of this study clarified the genetic make-up and evolutionary traits of the local population of tea, which gave some insight into the development of Lincang tea.